V. Fuchs, E. Hillary, La travesía de la Antártida. Expedición 1955-1958, Traducción de Julio F. Guillén, Madrid, Ediciones Cid, 1959, 320 p. - Martín, N. F. de (1960)
Fil: Martín, N. F. de. Universidad Nacional de Cuyo. Facultad de Filosofía y Letras